Prevalence Of Sella Turcica Morphology In Hypodivergent And Hyperdivergent Facial Growth Patterns - A Cephalometric Study (Journal of Pharmaceutical Negative Results, 2023)
Background: Sella turcica is the most commonly used landmarks in cephalometrics and is located at the centre of the cranium and is an important structure seen in the neurocranial and craniofacial region. The morphology of sella is important for the cephalometric position as a reference point when evaluating growth changes and progress in Orthodontic treatment . The aim of this study was to determine the correlation between the sellar characteristics and facial growth patterns.Material and Methods: A total of 90 cephalograms of the subjects reporting for Orthodontic treatment were collected, the cephalograms were divided into two groups. Group I consisting of 45 cephalograms with hypodivergent growth pattern and Group II consisting of 45 cephalograms with hyperdivergent growth pattern. Growth pattern was classified according to the mandibular plane as SN-MP >38° for hyperdivergent growth pattern and SN-MP <260 for hypodivergent growth pattern. Each cephalogram was traced manually on acetate paper using a tracing pencil and under optimal lighting conditions by same operator. In both the groups, shape, length, depth, diameter of the sella were determined. The data was tabulated in excel sheets and sent for statistical analysis. Mean, standard deviation and error were calculated. Independent t-test was used to determine the correlation between the variables.Results: The results revealed the length, depth, diameter of the sell was greater in the hyperdivergent growth pattern as compared to hypodivergent growth pattern. The length (p =0.0255 ) and diameter (p=0.0009) were statistically significant . Normal shape of sella was more prevalent in both group I &II (62.22% & 44.44%). Oblique morphologic shape was second most prevalent (33.33%) in hyperdivergent growth patternConclusion: This study concluded that a correlation exists between the two facial growth patterns and sella length and diameter. Length, diameter and depth are increased in hyperdivergent growth pattern as compared to hypodivergent growth pattern. Oblique shape was second most common in hyperdivergent growth pattern. Such studies are helpful in knowing the normal morphology of sella in various growth patterns which can help in cephalometric tracing, growth superimpositions as well as in growth forecasting and treatment planning in growing children.